DIVERSIFICATION OF FOREST FOOD PLANTS ON AGROFORESTRY SYSTEM IN KUNINGAN DISTRICT - Ai Nurlaila; Ika Karyaningsih; Nina Herlina (Journal of Forestry And Environment, 2018)
Dependence on food, especially carbohydrates can be reduced by digging for forest food sources, one of which is in the agroforestry system. This study aims to determine the diversity of forest food crops in agroforestry systems in Kuningan District, whether wild or cultivated. The method used for location determination is purposive sampling based on the location of agroforestry adjacent to the conservation area. The following villages 1) Cigugur Sub-district: Cisantana Village, Puncak Village, 2) Mandirancan Sub-district: Seda Village, Trijaya Village, 3) Darma Sub-district: Gunungsirah Village, Karangsari Village, and 4) Pasawahan Sub-District: Pasawahan Village, Desa Padabeunghar. Respondents were chosen based on purposive sampling which had land closest to conservation area with a minimum land of 0.25 ha. The result of the research is forestry food crop found in the agroforestry system in Kuningan District. Each is the plant as a source of carbohydrates as many as 6 species, plants as a source of fat as many as 5 species, and plants as a source of fruits as many as 19 species. The plants are almost evenly distributed in all villages, except for persimmon plants found only in Gunungsirah and Karangsari villages.Keywords: biodiversity, food plants, agroforestry, wild, cultivated